Macrophages and Fibroblasts, Key Players in Cancer Chemoresistance - Ireland, Lucy V.; Mielgo, Ainhoa (Frontiers in Cell and Developmental Biology, 2018)
Chemotherapy is routinely used in cancer treatment to eliminate primary and metastatic tumor cells. However, tumors often display or develop resistance to chemotherapy. Mechanisms of chemoresistance can be either tumor cell autonomous or mediated by the tumor surrounding non-malignant cells, also known as stromal cells, which include fibroblasts, immune cells, and cells from the vasculature. Therapies targeting cancer cells have shown limited effectiveness in tumors characterised by a rich tumor stroma. Tumor-associated macrophages (TAMs) and cancer-associated fibroblasts (CAFs) are the most abundant non-cancerous cells in the tumor stroma and have emerged as key players in cancer progression, metastasis and resistance to therapies. This review describes the recent advances in our understanding of how CAFs and TAMs confer chemoresistance to tumor cells and discusses the therapeutic opportunities of combining anti-tumor with anti-stromal therapies. The continued elucidation of the mechanisms by which TAMs and CAFs mediate resistance to therapies will allow the development of improved combination treatments for cancer patients.